RISE: Building a healthy nation via precision health at Integrative Pharmacogenomics Institute (iPROMISE) / Prof. Dr Mohd Zaki Salleh - Salleh, Mohd Zaki (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Precision Health leverages cutting-edge technologies to develop treatment and prevention strategies tailored to an individual's genetic makeup, environment, and lifestyle. Precision Health focuses on prediction, prevention, and precisely treatment of disease using individualized health strategies. They are that aligned with the vision and mission of ensuring that all individuals maintain good health and, as a result, our consequently productivity of the local population and longevity.